Brands Gamified: concept, applications and challenges - Malhotra , Suzanee (Gyan Management Journal, 2021)
Purpose: This article aims to contribute to build an understanding of the new concept of gamification that has made a buzz for itself recently. Despite being a trendy research topic, it still lacks sufficient literature studies to understand this concept from all angles. . This article initially aims to provide an introduction to this trendy concept along with its applications and examples.Proposed Design/Methodology/Approach: Inspired from Dr. Edward de Bono’s, six thinking hats this article provides a new and detailed analysis of the gamification concept from different angles. 12 Qualitative interviews were put to thematic data analysis under Nvivo software for coming to the research findings that are very interesting and one of its kind. Findings: The findings of this study are very crucial for brands involved and interested in the business of gamification. From the positive and creative sides that this concept offers, this paper has also indicated the negatives, facts and figures, feelings aspect as well as the planning required for this concept. Practical/Theoretical implications: With many new trends emerging in the world of digital marketing over the past couple of years, gamification has created a buzz for itself. An innovative yet appealing tool to attract consumers towards brands and keep them emotionally involved, it has been increasingly used across different types of brands. Originality/value: A novel approach for understanding the brand gamification concept on 6thinking hats approach is presented in the study. This article provides a base for future studies from an empirical angle in this domain that has not been taken up in this particular study. Limitations: This paper used qualitative study and the quantitative study has not been addressed in this article.